Rigid polyurethane foam composites based on iron tailing: Thermal stability, flame retardancy and fire toxicity. Issue 5 (September 2022) - Yang, Yadong; Shen, Haifeng; Luo, Yuzhou; Zhang, Renhui; Sun, Junjie; Liu, Xiuyu; Zong, Zhifang; Tang, Gang
In order to explore the potential utilization value of iron tailings, the typical solid waste-iron tailings was introduced into rigid polyurethane foam (RPUF) as a flame retardant filler in this paper. The flame retardant performance, combustion performance, gas-phase products and char residue's related properties of RPUF/ITS composites were systematically investigated by limiting oxygen index, thermogravimetric (TG), cone calorimetry (CCT) and thermogravimetric-infrared spectrometry (TG-FTIR). The results showed that ITS improved the overall thermal stability of the composites, and the T-5%, T-50%, Tmax1, Tmax2 and char residue rates were all higher than those of the pure samples. The CCT indicated that ITS had a certain effect on smoke suppression and heat release reduction. The peak heat release rate of RPUF-6 was reduced by 22.75% compared with that of the pure sample, and the total smoke release of RPUF-2 was reduced by 25.36%. Smoke factor (SF), fire growth rate index and fire performance index indicated that ITS reduced the fire risk of RPUF/ITS composites. TG-FTIR showed that ITS inhibited the decomposition of RPUF/ITS composites, and the release intensity of hydrocarbons, CO2, isocyanate compound, CO, aromatic compounds and esters decreased significantly. TG, MCC, scanning electron microscope and Raman implied that ITS promoted the formation of a dense char layer in RPUF and improved the heat resistance of the char layer.